New views on phototransduction from atomic force microscopy and single molecule force spectroscopy on native rods - Maity, Sourav (Sci Rep, 2017)
By combining atomic force microscopy (AFM) imaging and single-molecule force spectroscopy (SMFS), we analyzed membrane proteins of the rod outer segments (OS). With this combined approach we were able to study the membrane proteins in their natural environment. In the plasma membrane we identified native cyclic nucleotide-gated (CNG) channels which are organized in single file strings. We also identified rhodopsin located both in the discs and in the plasma membrane. SMFS reveals strikingly different mechanical properties of rhodopsin unfolding in the two environments. Molecular dynamic simulations suggest that this difference is likely to be related to the higher hydrophobicity of the plasma membrane, due to the higher cholesterol concentration. This increases rhodopsin mechanical stability lowering the rate of transition towards its active form, hindering, in this manner, phototransduction.